Optically active P5-deltacyclenes: selective oxidation, ligand properties, and a diastereoselective rearrangement reaction12. Issue 17 (7th April 2016) - Keller, I. C.; Bauer, W.; Heinemann, F. W.; Höhn, C.; Rohwer, L.; Zenneck, U.
Abstract : Tuning the ligand properties of chiral P–C cage compounds: selective mono oxidation of P5 -deltacyclene opens the gate to a phosphinious acid ligand. Abstract : Cage-chiral tetra- tert -butyl-P5 -deltacyclene5 is accessible as a pair of highly enriched enantiomers5′ and5′′ . The only secondary phosphorus atom P1 of the cage can be selectively oxidized by reaction with t -BuOOH. The P1-oxo species9a′ and9a′′, allow the direct determination of their ee values. Oxidation occurs with the complete retention of the optical activity of the compounds. The chiroptical properties of9a′ and9a′′ are strongly dominated by their cage chirality, the oxygen atom does not contribute significantly. Elemental sulfur and selenium oxidize P5 with high preference to yield P5-thio- and P5-seleno-P5 -deltacyclenes10 and11 of the intact cages again. Longer reaction time and more than stoichiometric amounts of selenium, leads to tri-seleno-P5 -tetracycloundecane12, a partially opened oxidized rearrangement product. The ligand properties of racemic9a were determined. Diphosphetane phosphorus atom P2 of9a is the active donor center to bind a Cr(CO)5 fragment, but a tautomerization of9a takes place if [(benzene)RuCl2 ]2 is added. A hydrogen atom migrates from P1 to the oxygen atom to form a phosphinous acid ligand. The lone pair of P1 is regenerated and acts as the active ligand function of the cage in this case. As for5, the base n -BuLi induces an efficient cage rearrangement reaction of9a, where P1 and the neighboring carbon atom C4 containing its t -Bu substituent change places. C4 moves to its new position without breaking the bond with P5, this way forming the novel P1-oxo-P5 -norsnoutene cage in a highly diastereoselective process.